Historical Analysis of Japanese Writing Systems Hiragana, Katakana, and Kanji - Harun, Yessy; Biduri, Febi Nur (Ridwan Institute, 2024)
This study discusses the historical analysis of the Japanese writing system hiragana, katakana, and kanji. In Japanese writing, there are three types of characters: kanji, hiragana, and katakana. Kanji, which are derived from Chinese characters, are used for words with specific meanings. Hiragana and katakana, are also used as grammatical particles, words without kanji equivalents, and foreign words. Hiragana is used for native Japanese words, while katakana is used for foreign words and emphasis. This study aims to determine the history of the development of the use of writing systems in Japan. The problem of this study is how the relationship between hiragana, katakana, and kanji in the Japanese writing system. The method used in this study is descriptive analysis. This research was obtained through literature studies sourced from history books, journals, articles, and research results from the formation of kanji itself. The results of this study show that historically, there is a relationship between katakana, hiragana, and kanji that complement each other and are important for the Japanese writing system.